PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN MAMUJU UTARA - Roniwati, Roniwati (Katalogis, 2016)
The aim of this study; (1) untuk mengetahui pengaruh simultaneous performance of the service quality of the vehicle testing bermotordi Department of Transportation, Communications and Information Technology of North Mamuju regency; (2) to determine the effect of partial performance of the service quality testing of motor vehicles in the Department of Transportation, Communications and Information Technology of North Mamuju regency. Theory of performance used from Kast and Rosenzweig (2002: 25), while the service quality theory from Parasuraman et al. (1988: 23). This type of research inikuantitatif. This study population pegawaidan society, where the number of employees 32 people, while in 1085 the community numbered drawn using the formula to 92 people. Employees using census sampling, while for people to use simple random sampling, and data analysis techniques using multiple linear regression. The results showed; (1) the effect of simultaneous kinerjaterhadap service quality testing of motor vehicles in the Department of Transportation, Communications and Information Technology of North Mamuju regency is determined by the dimensions of ability (ability), effort (effort), and the chance (opportunity), with the effect of 72.6% and tngkat a very strong relationship. This means that the rise of performance it will improve the quality of service. Descriptive analysis of the cumulative results show the ability (ability) has the highest percentage, especially on indicators of technological mastery, while the cumulative result is a low chance (opportunity) in terms of training opportunities; (2) The effect of partial kinerjaterhadap service quality testing of motor vehicles in the Department of Transportation, Communications and Information Technology of North Mamuju regency determined by ability (ability) significantly affects the quality of service. Effort (effort) significantly affects the quality of service, and the chance (opportunity) significantly affects the quality of service.